Zimnik 2023: Urban heritage and transformation of Usolye-Sibirskoye - Kozlov, Valery; Khomutinnikov, Ivan (project baikal, 2023)
The article outlines the results of the 24th International Baikal Winter Urban Planning Seminar of the International Baikal Winter University of Urban Planning Design in Irkutsk and Usolye-Sibirskoye. The comparative study shows how the teams developed a strategy for revitalising the Siberian city and searching for new socio-spatial opportunities. Participation of students in interdisciplinary project teams provides the opportunity not only to consolidate the academic material, but also to learn how to create promising ideas together, taking into account the demanding realities of urban planning. Such events help the experts look for new ideas and growth directions, and help the students gain insight into urban planning skills and teamwork. The article presents the viewpoints of the participants of the urban planning workshop, the methodology of teamwork in the current context of both analysis and the perspective of an indigenous Siberian city.
Keywords: innovations; creativity; future-oriented planning; team project work